Development of a Multidimensional Curriculum Evaluation Model for the Independent Curriculum in Elementary Schools - Hutahaean, Berman; Telaumbanua, Sadieli; Tamba, Losten (Lembaga Penerbitan dan Publikasi Ilmiah Program Pascasarjana IAI Sunan Giri Ponorogo, 2022)
This study aims to develop a multidimensional curriculum evaluation model (ECM) for the Independent Curriculum in Elementary Schools (SD). Independent Curriculum is a curriculum that allows teachers to design quality learning based on students’ needs and environment. It focuses on enhancing students’ character and competencies through the Pancasila student profile project. A comprehensive, systematic, and continuous evaluation model is required to ensure Independent Curriculum’s quality and relevance. The research method is R&D using the ADDIE model with five stages: analysis, design, development, implementation, and evaluation. The subjects are teachers, principals, supervisors, and curriculum experts. Data are collected through questionnaires, interviews, observations, and documentation. Data are analyzed quantitatively and qualitatively. The results show that ECM has six evaluation dimensions: context, input, process, product, impact, and meta-evaluation, which suit the Independent Curriculum’s characteristics in SD. ECM can evaluate various curriculum aspects: objectives, content, strategies, media, learning resources, assessment, learning outcomes, and curriculum impact. ECM also has a computer application program that simplifies the evaluation process and reporting. ECM receives positive feedback from the subjects and is valid, reliable, practical, and effective. The study concludes that ECM can improve Independent Curriculum quality in SD.